Buying into change : mass consumption, dictatorship, and democratization in Franco's Spain, 1939-1982 - Gómez del Moral, Alejandro J. (Lincoln : University of Nebraska Press, 2021)
Buying into Change examines how the development of a mass consumer society under the dictatorship of Generalissimo Francisco Franco (1939-1975) inserted Spain into transnational consumer networks and set the stage for Spain's transition to democracy during the late 1970s.
List of Illustrations -- Acknowledgments -- Introduction -- 1. World-Class Stores and (Inter)national Ambassadors -- 2. Imagining a New Señora Consumer -- 3. (Super)Marketing Western Modernity -- 4. "You Can Achieve Anything Nowadays If You Have Good Publicity" -- 5. "On That Day, Borders Did Not Exist" -- Epilogue -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Democratization -- Spain -- History -- 20th century; Consumers -- Spain -- History -- 20th century; Consumption (Economics) -- Social aspects -- Spain -- History -- 20th century; Spain -- Politics and government -- 1975-1982.; Spain -- Politics and government -- 1939-1975.; Démocratisation -- Espagne -- Histoire -- 20e siècle.; Espagne -- Politique et gouvernement -- 1975-1982.; Espagne -- Politique et gouvernement -- 1939-1975.; Consommateurs -- Espagne -- Histoire -- 20e siècle.; Société de consommation -- Aspect social -- Espagne -- Histoire -- 20e siècle.; HISTORY -- Europe -- Spain & Portugal; Politics and government; Democratization; Consumption (Economics) -- Social aspects; Consumers; Spain; 1900-1999; Electronic books; History